Exploring the use of information and communication technologies and social networks among university nursing faculty staff. An opinion survey - Fernández-Alemán, José Luis; Sánchez García, Ana Belén; López Montesinos, María José; Marqués-Sánchez, Pilar; Bayón Darkistade, Enrique; Pérez Rivera, Francisco Javier (Investigación y Educación en Enfermería, 2014)
Objective. This work sought to analyze the use of Information and Communication Technologies (ICTs) and social networks among the university nursing faculty staff in Spain. Methodology. This was a descriptive, cross-sectional study using a questionnaire on ICT skills designed to comply with the research objective, which was evaluated by experts and which was subjected to exploratory analysis of principal components; the reliability of this instrument measured with Cronbach’s alpha was 0.85. The information technology tool used to publish the questionnaire on line was Limesurvey. The sample comprised 165 professors from 25 Nursing Faculties and Schools from universities in Spain. Results. Seventy one percent of the total surveyed used internet services to look for information, 63% used the internet as a means for formation and learning, and 72% used it as a communication platform (e-mail and virtual platforms like Sakai and Moodle). Although 51% of the teaching staff surveyed had more than 120 students registered in their courses, hypothesis testing revealed that the number of students in class is not a determining factor for the teaching staff to have greater interest to update its knowledge in ICTs. Younger professors use new technologies more profusely and the most-valued advantage of using ICTs was quick access to information. Professors perceive that after the Bologna Declaration, which requires modifying their teaching-learning processes through the new teaching methodologies, a drop has been produced in their performance and that of their peers in their area of knowledge. Conclusion. The nursing teaching staff is making strong efforts to confront the new challenges posed by ICTs to train the professionals of the 21st century. It is fundamental to pay special attention to improving the university teaching staff’s skills in managing ICTs, promoting the implementation of the knowledge acquired. How to cite this article: Fernández-Alemán JL, Sánchez AB, LópezMJ, Marqués-Sánchez P, BayónE, Pérez FJ. Exploring the Use of information and communication technologies and social networks among university nursing faculty staff. An opinion survey. Invest Educ Enferm. 2014; 32(3):